A REVIEW OF RECENT MANAGEMENT AT RIAU UNIVERSITY LANGUAGE CENTRE, INDONESIA - Jismulatif; Marzuki (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2018)
This case study was focused on a review of the recent management of the language Centre programme, University of Riau. The data were collected using triangulation method where some instruments were used, two sets of questionnaires for the students and staff, a semi-structured interview for the three staff, the results of students’ exams, and policy documents. The findings provided the evidence that the students were more motivated to study English for their future employment (instrumental motivation), whereas the staffs were more motivated to teach English for intrinsic rewards rather than extrinsic rewards. The findings also showed that the quality of teaching was generally good but it was suggested that the number of the computer for CALL program be increased, and more importantly, among the staff and the Manager be continuously built for a strong teamwork which could positively affect the implementation of the programme.